2018
DOI: 10.1103/physrevlett.121.086803
|View full text |Cite
|
Sign up to set email alerts
|

Edge States and Topological Invariants of Non-Hermitian Systems

Abstract: The bulk-boundary correspondence is among the central issues of non-Hermitian topological states. We show that a previously overlooked "non-Hermitian skin effect" necessitates redefinition of topological invariants in a generalized Brillouin zone. The resultant phase diagrams dramatically differ from the usual Bloch theory. Specifically, we obtain the phase diagram of the non-Hermitian Su-Schrieffer-Heeger model, whose topological zero modes are determined by the non-Bloch winding number instead of the Bloch-H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
1,524
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,722 publications
(1,566 citation statements)
references
References 96 publications
35
1,524
4
3
Order By: Relevance
“…This anomalous localization was attributed to the proximity (in parameter space) to exceptional points with an order scaling with the system size in [48], an effect which was interpreted as an environment-mediated interaction effect. The same effect was confirmed analytically in [49] for a non-Hermitian SSH model with asymmetric hoppings and dubbed the non-Hermitian skin effect. Recently, Lee and Thomale [66] presented a characterization of these peculiar boundary modes and provided conditions for their existence.…”
Section: Extreme Defectiveness From Higher-order Exceptional Points Asupporting
confidence: 54%
See 1 more Smart Citation
“…This anomalous localization was attributed to the proximity (in parameter space) to exceptional points with an order scaling with the system size in [48], an effect which was interpreted as an environment-mediated interaction effect. The same effect was confirmed analytically in [49] for a non-Hermitian SSH model with asymmetric hoppings and dubbed the non-Hermitian skin effect. Recently, Lee and Thomale [66] presented a characterization of these peculiar boundary modes and provided conditions for their existence.…”
Section: Extreme Defectiveness From Higher-order Exceptional Points Asupporting
confidence: 54%
“…Together with Floquet systems, non-Hermitian lattices represent our first strong steps on the land of nonequilibrium, dynamical, topological phases. The departure from the Hermitian paradigm brings many surprises, like the fact that because of the extreme sensitivity to boundary conditions, a pristine non-Hermitian lattice may become devoid of extended states [47,48], an effect termed the non-Hermitian skin effect [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Further observations of a seemingly breakdown of the bulk-boundary correspondence principle [62,63] has led to proposals for a general classification of the topological phases of non-Hermitian systems [55,56,64]. A particular point of interest is the observation of the non-Hermitian skin effect [65][66][67][68][69][70][71], whereby all Eigen states of one-dimensional (1D) systems are localized at a boundary, in sharp contrast with the extend Bloch modes of Hermitian counterparts. This intriguing feature of non-Hermitian lattices has recently been experimentally demonstrated using topo electrical circuits [72] and quantum walks of single photons [73].…”
Section: Introductionmentioning
confidence: 99%
“…Topological phases and topological phase transitions in fermionic and bosonic systems, described by Hermitian Hamiltonians, have attracted great interests in past three decades [1][2][3]. Recent studies have revealed that topological phases can be extended to non-Hermitian systems beyond the scope of closed systems [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Especially, the interplay between non-Hermiticity and topological states leads to unique properties that have no counterparts in Hermitian systems [20,21].…”
Section: Introductionmentioning
confidence: 99%